1976
DOI: 10.1051/rnd:19760402
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in the Oestrogen Induced Lh Discharge of Ovariectomized Finnish Landrace and Scottish Blackface Ewes

Abstract: The discharge of LH following the injection of 50 j i g oestradiol benzoate was studied in i2 ovariectomized Blackface and 12 ovariectomized Finn ewes on 6 occasions (November, January, March, May, July and November). Both breeds were more sensitive to the oestradiol during the breeding season than during anoestrus. The Finn ewes were less sensitive than the Blackfaces as judged by the proportion of ewes discharging LH, the maximum plasma concentration of LH attained, the interval to the discharge of LH, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
1

Year Published

1977
1977
1986
1986

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 1 publication
4
31
1
Order By: Relevance
“…In castrated ewes, the interval between injection of oestradiol-17ß benzoate and the beginning of the LH discharge is independent of the time of year (Land et al, 1976), and the earlier discharge of LH in November may therefore simply be related to the earlier rise in oestrogen secretion. The lack of a preovulatory rise of oestradiol-17ß and LH in June presumably represents a failure of the hypothalamic-pituitary system to respond to withdrawal of luteal progesterone by secretion of FSH and LH in amounts sufficient to support the final matura¬ tion of the Graafian follicle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In castrated ewes, the interval between injection of oestradiol-17ß benzoate and the beginning of the LH discharge is independent of the time of year (Land et al, 1976), and the earlier discharge of LH in November may therefore simply be related to the earlier rise in oestrogen secretion. The lack of a preovulatory rise of oestradiol-17ß and LH in June presumably represents a failure of the hypothalamic-pituitary system to respond to withdrawal of luteal progesterone by secretion of FSH and LH in amounts sufficient to support the final matura¬ tion of the Graafian follicle.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the higher ovulation rates in certain breeds of sheep, e.g. Finnish Landrace, are associated with a relative insensitivity of the hypothalamic-pituitary system to the negative feedback effects of oestradiol (Land, Wheeler & Carr, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in (Land et al, 1976) and negative feedback may be increased (Legan & Karsch, 1979) (Roberts, Carlson & McCracken, 1976), and prolactin concentrations rise spectacularly during anoestrus (Ravault, 1976). Both of these responses may reflect a general change in spontaneous hypothalamic activity rather than a specific effect dependent upon steroids as discussed by Land & Carr (1979).…”
Section: Positive Feedbackmentioning
confidence: 98%
“…Seasonal anoestrus in sheep has been postulated to arise in part from a reduced sensitivity of the positive feedback response to oestrogen (Land, Wheeler & Carr, 1976). Since hyperprolactinaemia has also been reported to block the oestrogen-induced release of LH (Kann, Martinet & Schirar, 1978), and hyperprolactinaemia is a characteristic of anoestrous sheep (Walton, McNeilly, McNeilly & Cunningham, 1977), we have investigated the effects of reducing the prolactin concentrations in sheep during anoestrus with the dopamine agonist, bromocriptine.…”
Section: Introductionmentioning
confidence: 99%
“…The observation that LH release in ewes of high prolificacy was less sensitive to the beed-back effects of oestradiol (Land, Wheeler and Carr, 1976) (Findlay and Cumming, 1977 …”
mentioning
confidence: 99%